2010
DOI: 10.1021/ja106493h
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Stereoselective Synthesis of 9-Oxabicyclo[3.3.1]nona-4,7-dienes from Diverse 1-Oxo-4-oxy-5-ynes: A Viable Formal [4 + 2] Cycloaddition on ans-trans-Heterodiene Framework

Abstract: We report a highly stereoselective Au-catalyzed synthesis of 9-oxabicyclo[3.3.1]nona-4,7-dienes from diverse 1-oxo-4-oxy-5-ynes. Formation of these highly strained anti-Bredt oxacycles implies the workability of an unprecedented 1,4-dipole of s-trans-methylene(vinyl)oxonium. This work reveals the feasibility of a formal [4 + 2] cycloaddition on an s-trans-heterodiene framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In contrast to these examples that proceed through an initial endo-dig cyclization and generate gold–carbonyl ylide species, the group of Liu recently demonstrated that it is also possible to produce alternative, reactive, zwitterionic intermediates of type IV through an exo-dig cyclization process when using 1-oxo-5-ynes such as 3 and a cationic gold complex prepared in situ from P( t -Bu) 2 ( o -biphenyl)AuCl ( Au1 ) [39] and AgNTf 2 [40]. These dipolar intermediates undergo a cycloaddition with an external vinyl ether 4 , leading to interesting 9-oxabicyclo[3.3.1]nona-4,7-dienes 5 in good yields (Scheme 2).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to these examples that proceed through an initial endo-dig cyclization and generate gold–carbonyl ylide species, the group of Liu recently demonstrated that it is also possible to produce alternative, reactive, zwitterionic intermediates of type IV through an exo-dig cyclization process when using 1-oxo-5-ynes such as 3 and a cationic gold complex prepared in situ from P( t -Bu) 2 ( o -biphenyl)AuCl ( Au1 ) [39] and AgNTf 2 [40]. These dipolar intermediates undergo a cycloaddition with an external vinyl ether 4 , leading to interesting 9-oxabicyclo[3.3.1]nona-4,7-dienes 5 in good yields (Scheme 2).…”
Section: Reviewmentioning
confidence: 99%
“…A final elimination process regenerates the catalyst and affords the oxacyclic product 5 . Importantly, the reaction also proceeds with non-aromatic 1-oxo-4-alkoxy-5-ynes [40]. …”
Section: Reviewmentioning
confidence: 99%
“…Such cascade reactions have been well studied on various difunctionalized molecules including oxoalkynes [613], oxoallenes [14], oxoalkenes [15] and allenyl acetals [1618]. In this cascade sequence, two new rings and three chemical bonds are generated in a one-pot procedure.…”
Section: Introductionmentioning
confidence: 99%
“…(2)]. [5] With this catalyst mixture, we obtained azacyclic product 3a in 66% yield (entry 1). Our control experiment reveals that AgNTf 2 (5 mol%) alone implemented this cascade reaction to produce the same product in 58% yield (entry 2).…”
mentioning
confidence: 99%
“…Acetoxy (OAc) and methoxymethyl (MOM) ethers presumably exert an electron-withdrawing effect on the adja-cent alkyne to enhance the 6-exo-dig cyclization mode. [5] We prepared various 1-tosylhydrazon-4-acetoxy-5yne derivatives 4a-4e and 5a-5d to examine the generality of this exo-azacyclization/A C H T U N G T R E N N U N G [3+2] cycloaddition cascade. In a standard operation, these substrates were treated with ethoxyethene (4 equiv.)…”
mentioning
confidence: 99%